Secondary battery and electronic device

By setting through holes in the non-embedded lithium-ion current collector of the lithium-ion battery, the lithium ions are migrated to the non-embedded lithium-ion zone to participate in film formation, the problem of peeling and defiling of the material layer of the non-embedded lithium-ion battery under low temperature conditions is solved, and stable SEI film formation and kinetic performance are achieved.

CN119674181APending Publication Date: 2025-03-21XIAMEN AMPACE TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896588.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Under low temperature conditions, solvent co-embedding occurs in the non-embedded lithium region of the fast-charging graphite system in lithium-ion batteries, resulting in peeling and defiling of the material layer, affecting the structural integrity of the electrode assembly.

Method used

By setting through holes in the non-embedded lithium region current collector of the lithium-ion battery, lithium ions can be migrated to the non-embedded lithium region to participate in film formation, forming a stable SEI film, and reducing the embedding of solvent molecules.

Benefits of technology

It effectively improves the peeling and filming problem of material layer in the non-lithium-embedded area during low-temperature cycle of lithium-ion batteries, reduces the impact on the structural integrity of the electrode sheet during charging and discharging, and takes into account the dynamic performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674181A_ABST
    Figure CN119674181A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery and an electronic device, the secondary battery comprises an electrode assembly, the electrode assembly comprises a first pole piece and a second pole piece, the first pole piece comprises a first current collector, the second pole piece comprises a second current collector, the first current collector comprises a first section, and the first section is a part, which is not opposite to the second current collector, of at least one surface of the first current collector; the first pole piece further comprises a first material layer, the first material layer is arranged on at least part of the surface, deviating from the winding center of the electrode assembly, of the first section, and a plurality of first through holes are formed in the first section where the first material layer is arranged; the second pole piece further comprises a second material layer, and in the winding structure, the second material layer is arranged on the surface, deviating from the winding center of the electrode assembly and opposite to the multiple first through holes, of the second current collector. Through the arrangement, the problem that a material layer in a non-lithium-intercalation area is stripped and demolded when a fast-charging graphite system is in low-temperature circulation is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries represented by lithium-ion batteries have outstanding characteristics such as high energy density, long cycle life, low pollution, and no memory effect. At present, fast-charging graphite has become the preferred negative electrode active material in lithium-ion batteries because it can improve the charging performance and cycle life of lithium-ion batteries.

[0003] However, in lithium-ion batteries that use fast-charging graphite as the negative electrode active material, when cycling at low temperatures (temperature ≤ 10°C), the non-lithium intercalation area of ​​the electrode is prone to solvent co-intercalation during the charge and discharge process due to slow desolvation and insufficient film formation. When solvent co-intercalation is severe, the material layer in the non-lithium intercalation area will peel off and delaminate, resulting in convex spots on the appearance of the electrode assembly. Summary of the invention

[0004] The purpose of the present application is to provide a secondary battery and an electronic device that can effectively improve the problem of solvent co-intercalation in the non-lithium intercalation area of ​​a lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and delaminate. The specific technical solution is as follows:

[0005] It should be noted that in the invention content of the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0006] The first aspect of the present application provides a secondary battery, including an electrode assembly of a wound structure, the electrode assembly including a first electrode sheet and a second electrode sheet, the first electrode sheet including a first current collector, the second electrode sheet including a second current collector, along the length direction of the first electrode sheet after unfolding, the first current collector includes a first section, and along the winding direction of the electrode assembly, the first section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; the first electrode sheet also includes a first material layer, the first material layer is provided on at least part of the surface of the first section away from the winding center of the electrode assembly, and a plurality of first through holes are provided at the first section where the first material layer is provided; the second electrode sheet also includes a second material layer, and in the wound structure, the second current collector is provided with a second material layer on a surface away from the winding center of the electrode assembly and opposite to the plurality of first through holes. By setting a first through hole in an area where a first material layer is provided in the first section, during the charge and discharge process, the lithium ions received by the lithium-intercalated area on the first section can migrate through the first through hole to the non-lithium-intercalated area of ​​the first section to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalated area, reducing the embedding of solvent molecules, and effectively improving the problem of material layer peeling and film removal in the non-lithium-intercalated area of ​​the fast-charging graphite system during low-temperature cycling, thereby reducing the impact on the structural integrity of the first pole piece during the charge and discharge process and improving the quality of the first pole piece. At the same time, compared with the secondary battery system in which 1,3-propane sultone is added to the electrolyte to improve film formation, the film thickness of the lithium-intercalated area of ​​the present application is moderate, which reduces the risk of a decrease in the kinetic performance of the secondary battery due to excessive thickness of the SEI film in the lithium-intercalated area, thereby taking into account the kinetic performance of the secondary battery.

[0007] In one or more embodiments, based on the length of the first current collector, the length ratio of the first segment is L1, 2%≤L1≤20%. By regulating the length ratio of the first segment within the above range, during the charge and discharge process, the lithium ions received by the lithium-intercalation area on the first segment can migrate through the first through hole to the non-lithium-intercalation area of ​​the first segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalation area, reducing the embedding of solvent molecules, while taking into account the energy density and kinetic performance of the secondary battery, it is beneficial to improve the problem of material layer peeling and film removal in the non-lithium-intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0008] In one or more embodiments, along the length direction after the first pole piece is unfolded, and in the opposite direction of the winding direction, the first current collector also includes a second section and a third section connected in sequence, the second section is connected to the first section, and in the winding structure, the third section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; the third section is provided with a first material layer on at least part of the surface facing the winding center of the electrode assembly, and a plurality of second through holes are provided at the first material layer in the third section; the second current collector is provided with a second material layer on the surface facing the winding center and opposite to the plurality of second through holes. By providing the second through hole in the area where the first material layer is provided in the third section, a stable SEI film is formed on the surface of the non-lithium intercalation region, reducing the embedding of solvent molecules, thereby further improving the problem of material layer peeling and de-filming in the non-lithium intercalation region of the fast-charging graphite system during low-temperature cycling, and further reducing the impact on the structural integrity of the first pole piece during the charging and discharging process.

[0009] In one or more embodiments, based on the length of the first current collector, the length of the third segment accounts for L3, 2%≤L3≤20%. By adjusting the length of the third segment within the above range, a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, while taking into account the energy density and kinetic performance of the secondary battery, it is beneficial to improve the problem of material layer peeling and delamination in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0010] In one or more embodiments, along the width direction after the first pole piece is unfolded, the first current collector has a first edge and a second edge relative to each other, the width of the first current collector is M mm, the shortest distance between a single first through hole and the first edge or the second edge is m1 mm, 0≤m1≤M / 10, optionally, 1≤m1≤M / 20; and / or, the shortest distance between a single second through hole and the first edge or the second edge is m2 mm, 0≤m2≤M / 10, optionally, 1≤m2≤M / 20. By regulating the values ​​of m1 and m2 within the above range, the risk that the non-lithium intercalation regions of the first and third segments cannot effectively receive lithium ions is reduced, a stable SEI film is formed on the surface of the non-lithium intercalation region, and the embedding of solvent molecules is reduced, which is beneficial to improving the problem of material layer peeling and debonding in the non-lithium intercalation region of the fast-charging graphite system during low-temperature cycling.

[0011] In one or more embodiments, along the length direction after the first pole piece is unfolded, and along the winding direction of the electrode assembly, the first section has a relative third edge and a fourth edge, the third section has a relative fifth edge and a sixth edge, the length of the first current collector is L mm, the shortest distance between a single first through hole and the third edge is a1 mm, 0≤a1≤(L1×L) / 10, optionally, 1≤a1≤(L1×L) / 20; and / or, the shortest distance between a single second through hole and the sixth edge is a2 mm, 0≤a2≤(L3×L) / 10, optionally, 1≤a2≤(L3×L) / 20. By regulating the values ​​of a1 and a2 within the above range, it is beneficial for the non-lithium intercalation area of ​​the first section to receive lithium ions through the first through hole and the non-lithium intercalation area of ​​the third section to receive lithium ions through the second through hole, a stable SEI film is formed on the surface of the non-lithium intercalation area, the embedding of solvent molecules is reduced, and it is beneficial to improve the problem of material layer peeling and de-filming in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0012] In one or more embodiments, the shortest distance between a single first through hole and the fourth edge is b1 mm, 0≤b1≤(L1×L) / 20, optionally, 0≤b1≤(L1×L) / 40; and / or, the shortest distance between a single second through hole and the fifth edge is b2 mm, 0≤b2≤(L3×L) / 20, optionally, 0≤b2≤(L3×L) / 40. By regulating the values ​​of b1 and b2 within the above range, it is beneficial for the non-lithium intercalation area of ​​the first segment to receive lithium ions through the first through hole and the non-lithium intercalation area of ​​the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, which is beneficial to improve the problem of material layer peeling and delamination in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0013] In one or more embodiments, the diameter of the maximum circumscribed circle of the outer contour of a single first through hole on the surface of the first current collector is D1 μm, 2≤D1≤50, optionally, 5≤D1≤20; and / or, the diameter of the maximum circumscribed circle of the outer contour of a single second through hole on the surface of the first current collector is D2 μm, 2≤D2≤50, optionally, 5≤D2≤20. By regulating the values ​​of D1 and D2 within the above range, it is beneficial to improve the pass rate of lithium ions, and the lithium ions received by the lithium-intercalation area on the first segment can migrate to the non-lithium-intercalation area of ​​the first segment through the first through hole to participate in film formation, and the lithium ions received by the lithium-intercalation area on the third segment can migrate to the non-lithium-intercalation area of ​​the third segment through the second through hole to participate in film formation, which is beneficial to improve the problem of material layer peeling and demolding in the non-lithium-intercalation area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the processing performance of the secondary battery and improving the processing efficiency of the first current collector.

[0014] In one or more embodiments, along the length direction of the first pole piece after unfolding, the spacing between two adjacent first through holes is m'1 mm, 1.5D1≤m'1≤3D1; and / or, the spacing between two adjacent second through holes is m'2 mm, 1.5D2≤m'2≤3D2. By regulating the values ​​of m'1 and m'2 within the above range, it is beneficial to improve the uniformity of film formation in the non-lithium intercalation area, so that a stable and uniform SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, and is beneficial to improving the problem of material layer peeling and debonding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0015] In one or more embodiments, based on the surface area of ​​the first segment, the sum of the areas of the outer contours of the plurality of first through holes accounts for S1, 5%≤S1≤30%, optionally, 13%≤S1≤18%; and / or, based on the surface area of ​​the third segment, the sum of the areas of the outer contours of the plurality of second through holes accounts for S2, 5%≤S2≤30%, optionally, 13%≤S2≤18%. By regulating the values ​​of S1 and S2 within the above range, it is beneficial to improve the pass rate of lithium ions, so that a stable SEI film is formed on the surface of the non-lithium embedded area, reducing the embedding of solvent molecules, and is beneficial to improving the problem of material layer peeling and demolding in the non-lithium embedded area of ​​the fast-charging graphite system during low-temperature cycling, and the first current collector has good mechanical strength, while taking into account the processing efficiency of the first current collector.

[0016] In one or more embodiments, a first material layer is disposed on the entire surface of the first section facing away from the winding center of the electrode assembly; and / or, a first material layer is disposed on at least a portion of the surface of the first section facing toward the winding center of the electrode assembly; and / or, a first material layer is disposed on the entire surface of the third section facing toward the winding center of the electrode assembly; and / or, a first material layer is disposed on at least a portion of the surface of the third section facing away from the winding center of the electrode assembly.

[0017] In one or more embodiments, the first pole piece is a negative pole piece.

[0018] The second aspect of the present application provides an electronic device, comprising the secondary battery in any of the above embodiments. Thus, the electronic device of the present application has good performance.

[0019] Beneficial effects of the embodiments of the present application:

[0020] The embodiments of the present application provide a secondary battery and an electronic device. By setting a through hole on the current collector in the non-lithium insertion area of ​​the lithium ion battery, it is possible to effectively improve the problem of material layer peeling and demolding in the non-lithium insertion area while making the film thickness in the lithium insertion area moderate, taking into account the dynamic performance of the lithium ion battery.

[0021] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.

[0023] Figure 1 A schematic diagram of a winding structure formed by an electrode assembly in one embodiment of the present application;

[0024] Figure 2 This is a front view of the negative electrode sheet after the electrode assembly in another embodiment of the present application is unfolded.

[0025] Figure numerals: electrode assembly 001; positive electrode plate 10; positive electrode current collector 11; positive electrode material layer 12; negative electrode plate 20; negative electrode current collector 21; negative electrode material layer 22; separator 30; first edge 211; second edge 212; third edge 213; fourth edge 214; fifth edge 215; sixth edge 216; first through hole 2101; second through hole 2102. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0027] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0028] In the prior art, in lithium-ion batteries with fast-charging graphite as the negative electrode active material, when the structure of the electrode assembly is wound, it is usually required that the length or width of the negative electrode material layer can exceed the positive electrode material layer to prevent the generation of lithium precipitation, and the winding start section and the end section of the negative electrode plate are generally double-sided coated (that is, both sides of the current collector are coated with active material layers) to reduce the risk of powder loss and improve processing efficiency. However, when lithium-ion batteries with fast-charging graphite systems are cycled at low temperatures, the non-lithium intercalation area in the negative electrode plate is prone to solvent co-intercalation during the charge and discharge process due to slow desolvation speed and insufficient film formation, that is, the solvent molecules in the electrolyte enter the negative electrode material layer together with the lithium ions. Since the lithium ions and the solvent molecules form a strong coordination effect on the surface of the negative electrode, these solvent molecules enter the negative electrode together with the lithium ions, affecting the structure of the negative electrode material layer. When the solvent co-intercalation is serious, the non-lithium intercalation area will peel off and delaminate, resulting in convex spots on the appearance of the electrode assembly, destroying the structural integrity of the negative electrode material layer. It is understandable that the non-lithium intercalation area of ​​the negative electrode plate refers to: the portion of the negative electrode plate at least one side of which is not opposite to the positive electrode plate during the starting and ending sections of winding. At present, in order to improve the problem of peeling and demolding of the non-lithium intercalation area in the fast-charging graphite system, 1,3-propane sultone (PS) is generally added to the electrolyte to improve film formation, but the addition of PS will make the solid electrolyte interface (SEI) film in the lithium intercalation area thicker, which will cause the kinetic performance of the secondary battery to be greatly affected. Based on this, the present application provides a secondary battery and an electronic device that can improve the film-forming quality of the non-lithium intercalation area of ​​the plate in the lithium-ion battery while taking into account the kinetic performance of the secondary battery, and effectively improve the problem of peeling and demolding of the material layer in the non-lithium intercalation area of ​​the lithium-ion battery due to solvent co-intercalation. The specific technical solution is as follows:

[0029] The first aspect of the present application provides a secondary battery, including an electrode assembly of a wound structure, the electrode assembly including a first electrode sheet and a second electrode sheet, the first electrode sheet including a first current collector, the second electrode sheet including a second current collector, along the length direction of the first electrode sheet after unfolding, the first current collector includes a first section, and along the winding direction of the electrode assembly, the first section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; the first electrode sheet also includes a first material layer, the first material layer is provided on at least part of the surface of the first section away from the winding center of the electrode assembly, and a plurality of first through holes are provided at the first section where the first material layer is provided; the second electrode sheet includes a second material layer, and in the wound structure, the second current collector is provided with a second material layer on a surface away from the winding center of the electrode assembly and opposite to the plurality of first through holes.

[0030] The electrode assembly is defined as having an X direction for its length, a Y direction for its width, and a Z direction for its thickness when in the unfolded state. It is understood that the negative electrode sheet, the positive electrode sheet, and the separator have the same length, width, and thickness directions as the electrode assembly when in the unfolded state, and the winding direction of the electrode assembly is the W direction. For example, the first electrode sheet is the negative electrode sheet, and the second electrode sheet is the positive electrode sheet. Figure 1 to Figure 2 As shown, the electrode assembly 001 includes a positive electrode sheet 10, a negative electrode sheet 20 and a separator 30. The positive electrode sheet 10 includes a positive electrode collector 11 and a positive electrode material layer 12. The negative electrode sheet 20 includes a negative electrode collector 21 and a negative electrode material layer 22. Along the length direction (X direction) of the unfolded negative electrode sheet 20, the negative electrode collector 21 includes a first section, and along the winding direction (W direction) of the electrode assembly 001, the first section is a portion where at least one surface of the negative electrode collector 21 is not opposite to the positive electrode collector 11, that is, along the opposite direction of the winding direction (W direction), the winding tail end Q'' of the negative electrode sheet 20 is wound at least one circle to the portion aligned with the winding tail end Q of the positive electrode sheet 10, that is, along the winding direction (W direction), the first section is Q' to Q''. A negative electrode material layer 22 is disposed on the surface of the first section away from the winding center of the electrode assembly 001, and a plurality of first through holes 2101 are disposed at the first section where the first material layer 22 is disposed. In the winding structure, a positive electrode material layer 12 is disposed on the surface of the positive electrode current collector 11 away from the winding center of the electrode assembly 001 and opposite to the plurality of first through holes 2101. It should be noted that the number, size and spacing of the through holes in the figure are only for exemplary purposes.

[0031] In the wound electrode assembly of the present application, the first section is the portion of the first current collector that extends beyond the winding end of the second pole piece. When the secondary battery is charged and discharged, the first material layer on the surface of the first section away from the winding center of the electrode assembly has no lithium ions, so the first material layer on the surface of the first section away from the winding center of the electrode assembly is a non-lithium insertion area. The second current collector is provided with a second material layer on the surface away from the winding center of the electrode assembly and opposite to the plurality of first through holes. The first material layer on the surface of the first section facing the winding center of the electrode assembly is opposite to the provided second material layer, and there is lithium ion transmission, so the first material layer on the surface of the first section facing the winding center of the electrode assembly is a lithium insertion area. By setting a first through hole in an area where a first material layer is provided in the first section, during the charge and discharge process, the lithium ions received by the lithium-intercalated area on the first section can migrate through the first through hole to the non-lithium-intercalated area of ​​the first section to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalated area, reducing the embedding of solvent molecules, and effectively improving the problem of material layer peeling and film removal in the non-lithium-intercalated area of ​​the fast-charging graphite system during low-temperature cycling, thereby reducing the impact on the structural integrity of the first pole piece during the charge and discharge process and improving the quality of the first pole piece. At the same time, compared with the secondary battery system in which 1,3-propane sultone is added to the electrolyte to improve film formation, the film thickness of the lithium-intercalated area of ​​the present application is moderate, which reduces the risk of a decrease in the kinetic performance of the secondary battery due to excessive thickness of the SEI film in the lithium-intercalated area, thereby taking into account the kinetic performance of the secondary battery.

[0032] In one or more embodiments, based on the length of the first current collector, the length of the first segment accounts for L1, 2%≤L1≤20%. For example, the value of L1 can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of these values. By regulating the length of the first segment to be within the above range, during the charge and discharge process, the lithium ions received by the lithium-intercalated area on the first segment can migrate through the first through hole to the non-lithium-intercalated area of ​​the first segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalated area, reducing the embedding of solvent molecules, and at the same time helping to reduce the risk of the non-lithium-intercalated area at the tail end of the first pole piece being too long, which reduces the energy density and kinetic performance of the secondary battery. Thus, while taking into account the energy density and kinetic performance of the secondary battery, it is beneficial to improve the problem of material layer peeling and film removal in the non-lithium-intercalated area of ​​the fast-charging graphite system during low-temperature cycling.

[0033] In one or more embodiments, along the length direction of the first electrode sheet after unfolding and in the opposite direction of the winding direction, the first current collector also includes a second section and a third section connected in sequence, the second section is connected to the first section, and in the winding structure, the third section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; a first material layer is provided on at least part of the surface of the third section facing the winding center of the electrode assembly, and a plurality of second through holes are provided at the location where the first material layer is provided in the third section; a second material layer is provided on the surface of the second current collector facing the winding center and opposite to the plurality of second through holes. For example, Figure 1 to Figure 2 As shown, along the length direction (X direction) of the unfolded negative electrode plate 20, or along the opposite direction of the winding direction (W direction), the negative electrode current collector 21 also includes a second section and a third section connected in sequence, the second section is connected to the first section, and in the winding structure, the third section is a portion of at least one surface of the negative electrode current collector 21 that is not opposite to the positive electrode current collector 11, that is, along the winding direction (W direction), the winding starting end P'' of the negative electrode plate 20 is wound at least one circle to the portion aligned with the winding starting end P of the positive electrode plate 10, that is, the third section is P'' to P', and correspondingly, the second section is P' to Q'; a negative electrode material layer 22 is provided on the surface of the third section facing the winding center of the electrode assembly 001, and a plurality of second through holes 2102 are provided at the negative electrode material layer 22 in the third section. In the wound electrode assembly of the present application, the third section is a portion of at least one surface of the first current collector that is not opposite to the second current collector. When the secondary battery is charged and discharged, the first material layer on the surface of the third section facing the winding center of the electrode assembly does not receive lithium ions, so the first material layer on the surface of the third section facing the winding center of the electrode assembly is a non-lithium insertion area. The second current collector is provided with a second material layer on the surface facing the winding center of the electrode assembly and opposite to the plurality of second through holes. The first material layer on the surface of the third section away from the winding center of the electrode assembly is opposite to the provided second material layer, and there is lithium ion transmission, so the first material layer on the surface of the third section away from the winding center of the electrode assembly is a lithium insertion area. By setting a second through hole in the area where the first material layer is set in the third section, during the charge and discharge process, the lithium ions received by the lithium-embedded area on the third section can migrate through the second through hole to the non-lithium-embedded area of ​​the third section to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-embedded area, reducing the embedding of solvent molecules, thereby further improving the problem of material layer peeling and film removal in the non-lithium-embedded area of ​​the fast-charging graphite system during low-temperature cycling, further reducing the impact on the structural integrity of the first pole piece during the charge and discharge process, and at the same time, compared with the secondary battery system in which 1,3-propane sultone is added to the electrolyte to improve film formation, the film thickness of the lithium-embedded area of ​​the present application is moderate, taking into account the dynamic performance of the secondary battery. It should be noted that the number, size and spacing of the through holes in the figure are only for exemplary purposes.

[0034] In one or more embodiments, based on the length of the first current collector, the length of the third segment accounts for L3, 2%≤L3≤20%. For example, the value of L3 can be 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20% or a range consisting of any two of these values. By regulating the length of the third segment to be within the above range, during the charge and discharge process, the lithium ions received by the lithium-intercalated area on the third segment can migrate through the second through hole to the non-lithium-intercalated area of ​​the third segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalated area, reducing the embedding of solvent molecules, and at the same time helping to reduce the risk of the non-lithium-intercalated area at the starting end of the first pole piece being too long, thereby reducing the energy density and kinetic performance of the secondary battery. Thus, while taking into account the energy density and kinetic performance of the secondary battery, it is beneficial to improve the problem of material layer peeling and defilming in the non-lithium-intercalated area of ​​the fast-charging graphite system during low-temperature cycling.

[0035] In one or more embodiments, based on the length of the first current collector, the length of the second segment accounts for L2, 60%≤L2≤96%. For example, the value of L2 can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 96% or a range consisting of any two of these values. By regulating the length of the second segment to be within the above range, while improving the problem of material layer peeling in the non-lithium embedded area of ​​the fast-charging graphite system during low-temperature cycling, it is beneficial to take into account the energy density and kinetic performance of the secondary battery.

[0036] In one or more embodiments, along the width direction of the first pole piece after unfolding, the first current collector has a first edge and a second edge opposite to each other, the width of the first current collector is M mm, and the shortest distance between a single first through hole and the first edge or the second edge is m1 mm, for example, Figure 2 As shown, along the width direction (Y direction) after the negative electrode sheet 20 is unfolded, the negative electrode current collector 21 has a first edge 211 and a second edge 212 relative to each other, the width of the negative electrode current collector 21 is M mm, and the shortest distance between a single first through hole 2101 and the second edge 212 is m1 mm. 0≤m1≤M / 10, optionally, 1≤m1≤M / 20, for example, the value of m1 can be 0, 0.3, 0.5, 0.8, 1, M / 20, M / 18, M / 15, M / 12, M / 10 or a range consisting of any two of the values. By regulating the value of m1 within the above range, the risk of the non-lithium insertion area of ​​the first segment being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium insertion area of ​​the first segment to receive lithium ions through the first through hole, and a stable SEI film is formed on the surface of the non-lithium insertion area, reducing the embedding of solvent molecules, which is beneficial to improve the problem of material layer peeling and film removal in the non-lithium insertion area of ​​the fast-charging graphite system during low-temperature cycling.

[0037] In one or more embodiments, along the width direction of the first pole piece after unfolding, the first current collector has a first edge and a second edge opposite to each other, the width of the first current collector is M mm, and the shortest distance between a single second through hole and the first edge or the second edge is m2 mm, for example, Figure 2 As shown, along the width direction (Y direction) after the negative electrode sheet 20 is unfolded, the negative electrode current collector 21 has a first edge 211 and a second edge 212 relative to each other, the width of the negative electrode current collector 21 is M mm, and the shortest distance between a single second through hole 2102 and the first edge 211 is m2 mm. 0≤m2≤M / 10, optionally, 1≤m2≤M / 20, for example, the value of m2 can be 0, 0.3, 0.5, 0.8, 1, M / 20, M / 18, M / 15, M / 12, M / 10 or a range consisting of any two of the values. By regulating the value of m2 within the above range, the risk of the non-lithium insertion area of ​​the third segment being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium insertion area of ​​the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium insertion area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and film removal in the non-lithium insertion area of ​​the fast-charging graphite system during low-temperature cycling.

[0038] In one or more embodiments, along the width direction of the first pole piece after unfolding, the first current collector has a first edge and a second edge relative to each other, the width of the first current collector is M mm, the shortest distance between a single first through hole and the first edge or the second edge is m1 mm, 0≤m1≤M / 10, optionally, 1≤m1≤M / 20, for example, the value of m1 can be 0, 0.3, 0.5, 0.8, 1, M / 20, M / 18, M / 15, M / 12, M / 10 or a range consisting of any two of the values ​​therein; and, the shortest distance between a single second through hole and the first edge or the second edge is m2 mm, 0≤m2≤M / 10, optionally, 1≤m2≤M / 20, for example, the value of m2 can be 0, 0.3, 0.5, 0.8, 1, M / 20, M / 18, M / 15, M / 12, M / 10 or a range consisting of any two of the values ​​therein. By regulating the values ​​of m1 and m2 within the above range, the risk of the non-lithium intercalation areas of the first and third segments being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation areas of the first segment to receive lithium ions through the first through hole and the non-lithium intercalation areas of the third segment to receive lithium ions through the second through hole. A stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0039] In one or more embodiments, along the length direction of the first pole piece after unfolding and along the winding direction of the electrode assembly, the first section has a third edge and a fourth edge opposite to each other, the third section has a fifth edge and a sixth edge opposite to each other, the length of the first current collector is L mm, and the shortest distance between a single first through hole and the third edge is a1 mm, for example, as Figure 2 As shown, along the length direction (X direction) of the unfolded negative electrode sheet 20 and along the winding direction (W direction) of the electrode assembly 001, the first section has a third edge 213 and a fourth edge 214 opposite to each other, the third section has a fifth edge 215 and a sixth edge 216 opposite to each other, the length of the negative electrode collector 21 is L mm, and the shortest distance between a single first through hole 2101 and the third edge 213 is a1 mm. 0≤a1≤(L1×L) / 10, optionally, 1≤a1≤(L1×L) / 20. For example, the value of a1 can be 0, 0.3, 0.5, 0.8, 1, (L1×L) / 20, (L1×L) / 18, (L1×L) / 15, (L1×L) / 12, (L1×L) / 10, or a range consisting of any two of these values. By adjusting the value of a1 within the above range, the risk of the non-lithium intercalation area of ​​the first section being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation area of ​​the first section to receive lithium ions through the first through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0040] In one or more embodiments, along the length direction of the first pole piece after unfolding and along the winding direction of the electrode assembly, the first section has a third edge and a fourth edge opposite to each other, the third section has a fifth edge and a sixth edge opposite to each other, the length of the first current collector is L mm, and the shortest distance between a single second through hole and the sixth edge is a2 mm, for example, as Figure 2As shown, along the length direction (X direction) of the unfolded negative electrode sheet 20 and along the winding direction (W direction) of the electrode assembly 001, the first section has a third edge 213 and a fourth edge 214 opposite to each other, the third section has a fifth edge 215 and a sixth edge 216 opposite to each other, the length of the negative electrode current collector 21 is L mm, and the shortest distance between a single second through hole 2102 and the sixth edge 216 is a2 mm. 0≤a2≤(L3×L) / 10, optionally, 1≤a2≤(L3×L) / 20. For example, the value of a2 can be 0, 0.3, 0.5, 0.8, 1, (L3×L) / 20, (L3×L) / 18, (L3×L) / 15, (L3×L) / 12, (L3×L) / 10, or a range consisting of any two of these values. By regulating the value of a2 within the above range, the risk of the non-lithium intercalation area of ​​the third segment being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation area of ​​the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0041] In one or more embodiments, along the length direction of the first pole piece after unfolding and along the winding direction of the electrode assembly, the first section has a third edge and a fourth edge relative to each other, the third section has a fifth edge and a sixth edge relative to each other, the length of the first current collector is L mm, the shortest distance between a single first through hole and the third edge is a1 mm, 0≤a1≤(L1×L) / 10, optionally, 1≤a1≤(L1×L) / 20, for example, the value of a1 can be 0, 0.3, 0.5, 0.8, 1, (L1×L) / 20, (L1×L) / 18, (L1×L) / 15, (L1×L) / 12, (L1×L) / 10 or a range consisting of any two of the values ​​therein; and, the shortest distance between a single second through hole and the sixth edge is a2 mm, 0≤a2≤(L3×L) / 10, optionally, 1≤a2≤(L3×L) / 20, for example, the value of a2 can be 0, 0.3, 0.5, 0.8, 1, (L3×L) / 20, (L3×L) / 18, (L3×L) / 15, (L3×L) / 12, (L3×L) / 10 or a range consisting of any two of these values. By regulating the values ​​of a1 and a2 within the above range, the risk that the non-lithium intercalation areas of the first and third segments cannot effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation areas of the first segment to receive lithium ions through the first through hole and the non-lithium intercalation areas of the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, which reduces the embedding of solvent molecules, and is beneficial to improve the problem of material layer peeling and debonding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0042] In one or more embodiments, the shortest distance between a single first through hole and the fourth edge is b1 mm, for example, Figure 2 As shown, the shortest distance between a single first through hole 2101 and the fourth edge 214 is b1 mm. 0≤b1≤(L1×L) / 20, optionally, 0≤b1≤(L1×L) / 40, for example, the value of b1 can be 0, (L1×L) / 40, (L1×L) / 38, (L1×L) / 35, (L1×L) / 32, (L1×L) / 30, (L1×L) / 28, (L1×L) / 25, (L1×L) / 22, (L1×L) / 20 or a range consisting of any two of the values. By regulating the value of b1 within the above range, the risk of the non-lithium insertion area of ​​the first segment being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium insertion area of ​​the first segment to receive lithium ions through the first through hole, and a stable SEI film is formed on the surface of the non-lithium insertion area, reducing the embedding of solvent molecules, which is beneficial to improve the problem of material layer peeling and debonding in the non-lithium insertion area of ​​the fast-charging graphite system during low-temperature cycling.

[0043] In one or more embodiments, the shortest distance between a single second through hole and the fifth edge is b2 mm, for example, Figure 2 As shown, the shortest distance between a single second through hole 2102 and the fifth edge 215 is b2 mm. 0≤b2≤(L3×L) / 20, optionally, 0≤b2≤(L3×L) / 40. For example, the value of b2 can be 0, (L3×L) / 40, (L3×L) / 38, (L3×L) / 35, (L3×L) / 32, (L3×L) / 30, (L3×L) / 28, (L3×L) / 25, (L3×L) / 22, (L3×L) / 20 or a range consisting of any two of the values. By regulating the value of b2 within the above range, the risk of the non-lithium intercalation area of ​​the third segment being unable to effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation area of ​​the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and debonding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0044] In one or more embodiments, the shortest distance between a single first through hole and the fourth edge is b1 mm, 0≤b1≤(L1×L) / 20, optionally, 0≤b1≤(L1×L) / 40, for example, the value of b1 can be 0, (L1×L) / 40, (L1×L) / 38, (L1×L) / 35, (L1×L) / 32, (L1×L) / 30, (L1×L) / 28, (L1×L) / 25, (L1×L) / 22, (L1×L) / 20 or a range consisting of any two of the values; and, the shortest distance between a single second through hole and the fifth edge is b2 mm, 0≤b2≤(L3×L) / 20, optionally, 0≤b2≤(L3×L) / 40, for example, the value of b2 can be 0, (L3×L) / 40, (L3×L) / 38, (L3×L) / 35, (L3×L) / 32, (L3×L) / 30, (L3×L) / 28, (L3×L) / 25, (L3×L) / 22, (L3×L) / 20 or a range consisting of any two of these values. By regulating the values ​​of b1 and b2 within the above range, the risk that the non-lithium intercalation areas of the first and third segments cannot effectively receive lithium ions is reduced, which is beneficial for the non-lithium intercalation areas of the first segment to receive lithium ions through the first through hole and the non-lithium intercalation areas of the third segment to receive lithium ions through the second through hole, and a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and debonding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling.

[0045] In one or more embodiments, the diameter of the maximum circumscribed circle of the outer contour of a single first through hole on the surface of the first current collector is D1 μm, for example, Figure 2 As shown, the diameter of the maximum circumscribed circle of the outer contour of a single first through hole 2101 on the surface of the negative electrode current collector 21 is D1 μm. 2≤D1≤50, optionally, 5≤D1≤20, for example, the value of D1 can be 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50 or a range consisting of any two of the values. By regulating the value of D1 within the above range, it is beneficial to improve the pass rate of lithium ions, and the lithium ions received by the lithium-insertion area on the first section can migrate through the first through hole to the non-lithium-insertion area of ​​the first section to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-insertion area, reducing the embedding of solvent molecules, which is beneficial to improve the problem of material layer peeling and demolding in the non-lithium-insertion area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the processing performance of the secondary battery and improving the processing efficiency of the first current collector.

[0046] In one or more embodiments, the diameter of the maximum circumscribed circle of the outer contour of a single second through hole on the surface of the first current collector is D2 μm, for example, Figure 2As shown, the diameter of the maximum circumscribed circle of the outer contour of a single second through hole 2102 on the surface of the negative electrode current collector 21 is D2 μm. 2≤D2≤50, optionally, 5≤D2≤20, for example, the value of D2 can be 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50 or a range consisting of any two of the values. By regulating the value of D2 within the above range, it is beneficial to improve the pass rate of lithium ions, and the lithium ions received by the lithium-insertion area on the third segment can migrate through the second through hole to the non-lithium-insertion area of ​​the third segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-insertion area, reducing the embedding of solvent molecules, which is beneficial to improve the problem of material layer peeling and film removal in the non-lithium-insertion area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the processing performance of the secondary battery and improving the processing efficiency of the first current collector.

[0047] In one or more embodiments, the diameter of the maximum circumscribed circle of the outer contour of a single first through hole on the surface of the first current collector is D1 μm, 2≤D1≤50, optionally, 5≤D1≤20, for example, the value of D1 can be 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50 or a range consisting of any two of the values; and, the diameter of the maximum circumscribed circle of the outer contour of a single second through hole on the surface of the first current collector is D2 μm, 2≤D2≤50, optionally, 5≤D2≤20, for example, the value of D2 can be 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50 or a range consisting of any two of the values. By regulating the values ​​of D1 and D2 within the above range, the pass rate of lithium ions can be improved. The lithium ions received by the lithium-intercalating area on the first segment can migrate to the non-lithium-intercalating area of ​​the first segment through the first through hole to participate in film formation, and the lithium ions received by the lithium-intercalating area on the third segment can migrate to the non-lithium-intercalating area of ​​the third segment through the second through hole to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalating area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium-intercalating area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the processing performance of the secondary battery and improving the processing efficiency of the first current collector.

[0048] In one or more embodiments, along the length direction of the first pole piece after it is unfolded, the distance between two adjacent first through holes is m'1 mm, for example, Figure 2As shown, along the length direction (X direction) of the unfolded negative electrode sheet 20, the spacing between two adjacent first through holes 2101 is m'1 mm. 1.5D1≤m'1≤3D1, for example, the value of m'1 can be 1.5D1, 1.8D1, 2D1, 2.2D1, 2.5D1, 2.8D1, 3D1 or a range consisting of any two of these values. By regulating the value of m'1 within the above range, the lithium ions received by the lithium-intercalation area on the first segment migrate through the first through hole to the non-lithium-intercalation area of ​​the first segment to participate in film formation, which is beneficial to improve the uniformity of film formation in the non-lithium-intercalation area, so that a stable and uniform SEI film is formed on the surface of the non-lithium-intercalation area, reducing the embedding of solvent molecules, and is beneficial to improve the problem of material layer peeling and film removal in the non-lithium-intercalation area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the actual production of secondary batteries.

[0049] In one or more embodiments, the distance between two adjacent second through holes is m'2 mm, for example, Figure 2 As shown, along the length direction (X direction) after the negative electrode sheet 20 is unfolded, the spacing between two adjacent second through holes 2102 is m'2 mm. 1.5D2≤m'2≤3D2, for example, the value of m'2 can be 1.5D2, 1.8D2, 2D2, 2.2D2, 2.5D2, 2.8D2, 3D2 or a range consisting of any two values ​​therein. By regulating the value of m'2 within the above range, the lithium ions received by the lithium-intercalation area on the third segment migrate through the second through holes to the non-lithium-intercalation area of ​​the third segment to participate in film formation, which is beneficial to improve the uniformity of film formation in the non-lithium-intercalation area, so that a stable and uniform SEI film is formed on the surface of the non-lithium-intercalation area, reducing the embedding of solvent molecules, which is beneficial to improve the problem of material layer peeling and film removal in the non-lithium-intercalation area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the actual production of secondary batteries.

[0050] In one or more embodiments, along the length direction of the first pole piece after unfolding, the spacing between two adjacent first through holes is m'1 mm, 1.5D1≤m'1≤3D1, for example, the value of m'1 can be 1.5D1, 1.8D1, 2D1, 2.2D1, 2.5D1, 2.8D1, 3D1 or a range consisting of any two of these values; and, the spacing between two adjacent second through holes is m'2 mm, 1.5D2≤m'2≤3D2, for example, the value of m'2 can be 1.5D2, 1.8D2, 2D2, 2.2D2, 2.5D2, 2.8D2, 3D2 or a range consisting of any two of these values. By regulating the values ​​of m'1 and m'2 within the above range, the lithium ions received by the lithium intercalation area on the first segment migrate through the first through hole to the non-lithium intercalation area of ​​the first segment to participate in film formation, and the lithium ions received by the lithium intercalation area on the third segment migrate through the second through hole to the non-lithium intercalation area of ​​the third segment to participate in film formation, which is beneficial to improving the uniformity of film formation in the non-lithium intercalation area, so that a stable and uniform SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the actual production of secondary batteries.

[0051] In the present application, the spacing between two adjacent through holes refers to the distance between the centers of the circumscribed circles of the outer contours of the two adjacent through holes along the length direction of the unfolded first pole piece.

[0052] In one or more embodiments, based on the surface area of ​​the first segment, the sum of the areas of the outer contours of the plurality of first through holes accounts for S1, 5%≤S1≤30%, optionally, 13%≤S1≤18%, for example, the value of S1 may be 5%, 8%, 10%, 12%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of these values. By regulating the value of S1 within the above range, it is beneficial to improve the pass rate of lithium ions, and the lithium ions received by the lithium-embedded area on the first segment migrate through the first through hole to the non-lithium-embedded area of ​​the first segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-embedded area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium-embedded area of ​​the fast-charging graphite system during low-temperature cycling, and the first current collector has good mechanical strength, while taking into account the processing efficiency of the first current collector.

[0053] In one or more embodiments, based on the surface area of ​​the third segment, the sum of the areas of the outer contours of the plurality of second through holes accounts for S2, 5%≤S2≤30%, optionally, 13%≤S2≤18%, for example, the value of S2 may be 5%, 8%, 10%, 12%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of these values. By regulating the value of S2 within the above range, it is beneficial to improve the pass rate of lithium ions, and the lithium ions received by the lithium-embedded area on the third segment migrate through the second through holes to the non-lithium-embedded area of ​​the third segment to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-embedded area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium-embedded area of ​​the fast-charging graphite system during low-temperature cycling, and the first current collector has good mechanical strength, while taking into account the processing efficiency of the first current collector.

[0054] In one or more embodiments, based on the surface area of ​​the first segment, the sum of the areas of the outer contours of the plurality of first through holes accounts for S1, 5%≤S1≤30%, optionally, 13%≤S1≤18%, for example, the value of S1 may be 5%, 8%, 10%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of the values ​​therein; and, based on the surface area of ​​the third segment, the sum of the areas of the outer contours of the plurality of second through holes accounts for S2, 5%≤S2≤30%, optionally, 13%≤S2≤18%, for example, the value of S2 may be 5%, 8%, 10%, 13%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range consisting of any two of the values ​​therein. By regulating the values ​​of S1 and S2 within the above range, the pass rate of lithium ions is improved. The lithium ions received by the lithium intercalation area on the first segment migrate to the non-lithium intercalation area of ​​the first segment through the first through hole to participate in film formation, and the lithium ions received by the lithium intercalation area on the third segment migrate to the non-lithium intercalation area of ​​the third segment through the second through hole to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium intercalation area, reducing the embedding of solvent molecules, which is beneficial to improving the problem of material layer peeling and demolding in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling, and the first current collector has good mechanical strength, while taking into account the processing efficiency of the first current collector.

[0055] In one or more embodiments, the first section is provided with a first material layer on the entire surface away from the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on at least a portion of the surface toward the winding center of the electrode assembly. In one or more embodiments, the third section is provided with a first material layer on the entire surface toward the winding center of the electrode assembly. In one or more embodiments, the third section is provided with a first material layer on at least a portion of the surface away from the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on the entire surface away from the winding center of the electrode assembly; and, the first section is provided with a first material layer on at least a portion of the surface toward the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on the entire surface away from the winding center of the electrode assembly; and, the third section is provided with a first material layer on the entire surface toward the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on the entire surface away from the winding center of the electrode assembly; and, the third section is provided with a first material layer on the entire surface away from the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on at least a portion of the surface toward the winding center of the electrode assembly; and, the third section is provided with a first material layer on the entire surface toward the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on at least a portion of the surface facing the winding center of the electrode assembly; and, the third section is provided with a first material layer on at least a portion of the surface facing away from the winding center of the electrode assembly. In one or more embodiments, the third section is provided with a first material layer on the entire surface facing the winding center of the electrode assembly; and, the third section is provided with a first material layer on at least a portion of the surface facing away from the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on the entire surface facing away from the winding center of the electrode assembly; and, the first section is provided with a first material layer on at least a portion of the surface facing away from the winding center of the electrode assembly; and, the third section is provided with a first material layer on the entire surface facing away from the winding center of the electrode assembly. In one or more embodiments, the first section is provided with a first material layer on the entire surface facing away from the winding center of the electrode assembly; and, the first section is provided with a first material layer on at least a portion of the surface facing away from the winding center of the electrode assembly; and, the third section is provided with a first material layer on at least a portion of the surface facing away from the winding center of the electrode assembly. In one or more embodiments, a first material layer is disposed on at least a portion of the surface of the first section toward the winding center of the electrode assembly; and / or, a first material layer is disposed on the entire surface of the third section toward the winding center of the electrode assembly; and / or, a first material layer is disposed on at least a portion of the surface of the third section away from the winding center of the electrode assembly.In one or more embodiments, a first material layer is disposed on the entire surface of the first section facing away from the winding center of the electrode assembly; and, a first material layer is disposed on at least a portion of the surface of the first section facing toward the winding center of the electrode assembly; and, a first material layer is disposed on the entire surface of the third section facing toward the winding center of the electrode assembly; and, a first material layer is disposed on at least a portion of the surface of the third section facing away from the winding center of the electrode assembly.

[0056] Through the above-mentioned arrangement, the lithium ions received by the lithium-intercalated area migrate to the non-lithium-intercalated area through the first through hole to participate in film formation, so that a stable SEI film is formed on the surface of the non-lithium-intercalated area, reducing the embedding of solvent molecules, improving the problem of material layer peeling and defilming in the non-lithium-intercalated area of ​​the fast-charging graphite system during low-temperature cycling, while taking into account the energy density and kinetic performance of the secondary battery.

[0057] In one or more embodiments, the first electrode is a negative electrode. When the first electrode is a negative electrode, it is beneficial to improve the problem of graphite exfoliation and delamination in the non-lithium intercalation area of ​​the fast-charging graphite system during low-temperature cycling, thereby improving the structural stability and integrity of the negative electrode.

[0058] In one or more embodiments, along the length direction after the first pole piece is unfolded, the first through holes and the second through holes arranged on the first section and the third section of the first current collector are distributed in a matrix. In the present application, along the width direction after the first pole piece is unfolded, multiple rows of first through holes and second through holes are arranged in the first section and the third section, and the spacing between the corresponding through holes in each row is equal. The present application does not have any special restrictions on the number of rows of through holes. Those skilled in the art can set them according to the actual specifications of the first pole piece, as long as the purpose of the present application can be achieved. For example, the number of rows of first through holes arranged on the first section of the first current collector can be 2000 to 20000 rows; the number of rows of second through holes arranged on the third section of the first current collector can be 2000 to 20000 rows.

[0059] In one or more embodiments, the shape of the outer contour of a single first through hole or a second through hole includes one of a circle, an ellipse or a polygon. In the present application, there is no particular limitation on the shape of the polygon, as long as the purpose of the present application can be achieved. For example, the shape of the outer contour of a single through hole can be independently selected from one of a triangle, a rectangle, a trapezoid, a square, a pentagon or a hexagon. By adjusting the shape of the outer contour of the first through hole or the second through hole, the actual processing difficulty is reduced and the actual production efficiency is improved.

[0060] In the present application, when the first pole piece is a negative pole piece, the first current collector is a negative current collector, and the first material layer is a negative material layer. The present application has no particular restrictions on the negative current collector, as long as the purpose of the present application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector. For example, the composite current collector can be a lithium copper composite current collector, a carbon copper composite current collector, a nickel copper composite current collector, a titanium copper composite current collector, etc. The negative electrode material layer includes a negative electrode active material, and the negative electrode active material may include but is not limited to at least one of artificial graphite or natural graphite with a coating layer, and the coating layer includes a coating material, and the coating material includes one of a carbon material, an oxide or a polymer; the carbon material includes at least one of carbon nanotubes, graphene, carbon fiber, carbon black or pyrolytic carbon, the oxide includes at least one of silicon dioxide, aluminum oxide, titanium oxide or zinc oxide, and the polymer includes at least one of polyacrylonitrile, polyaniline, polypyrrole, polyvinyl alcohol or polyimide. In the present application, the coating layer is completely coated on the surface of the particles of the graphite material (i.e., artificial graphite and / or natural graphite). At least part of the above-mentioned "complete coating" is homogeneous layer coating, that is, at least part of the coating layer is uniformly coated on the surface of the particles of the graphite material with uniform thickness. The present application has no special restrictions on the mass percentage of the coating layer, as long as the purpose of the present application can be achieved. For example, based on the mass of the negative electrode active material, the mass percentage of the coating layer can be 5% to 15%. The present application has no special restrictions on the average thickness of the coating layer, as long as the purpose of the present application can be achieved. For example, the average thickness of the coating layer can be 10nm to 100nm. In one or more embodiments, artificial graphite and / or natural graphite with a coating layer is assembled into a button cell as a negative electrode active material, and the button cell is charged to 4.35V at a constant current of 2C, and then charged to 0.05C at a constant voltage of 4.35V, and discharged to 2.4V at a constant current of 0.5C. This is one charge and discharge cycle, and the cycle capacity retention rate of the button cell after 10 cycles of charge and discharge is ≥80%. At this time, artificial graphite and / or natural graphite with a coating layer is used as a negative electrode active material in a secondary battery, and the secondary battery has good fast charging performance. The present application has no particular restrictions on the preparation method of the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the commercially available negative electrode active material required for the present application can be selected in combination with the "test of the thickness of the coating layer", "test of the mass percentage of the coating layer" and "fast-charging graphite performance test" in the present application. In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. Optionally, the negative electrode material layer may further include a conductive agent and a negative electrode binder. The present application has no particular limitation on the type of the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved.For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application does not particularly limit the type of negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. Optionally, the negative electrode material layer also includes a thickener. The present application does not particularly limit the type of thickener, as long as the purpose of the present application can be achieved. For example, the thickener may include at least one of carboxymethyl cellulose or sodium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, conductive agent, negative electrode binder and thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0061] In the present application, when the first electrode sheet is a negative electrode sheet, the second electrode sheet is a positive electrode sheet. The second current collector is a positive current collector, and the second material layer is a positive electrode material layer. The present application has no special restrictions on the positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer of the present application contains positive electrode active materials. The present application has no special restrictions on the type of positive electrode active materials, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05O2 (NCM955), NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate or lithium iron manganese phosphate. In the present application, the positive electrode active material may also contain non-metallic elements, for example, the non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. In the present application, the positive electrode material layer may also include a positive electrode binder and a conductive agent. The present application does not particularly limit the type of the positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may be the same as the type of the negative electrode binder in the above-mentioned negative electrode material layer. The present application does not particularly limit the type of the conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be the same as the type of the conductive agent in the above-mentioned negative electrode material layer. The present application has no particular restriction on the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0062] The present application does not have any particular restrictions on the preparation method of the first electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the first electrode sheet may include but is not limited to the following steps: (1) pre-winding the first current collector and the prepared second electrode sheet, determining the surface of the first current collector facing the electrode assembly, the surface facing away from the electrode assembly, and the first section, the second section, and the third section, and setting a first through hole on the first section; (2) preparing a first slurry; (3) applying the first slurry on the surface of the first current collector facing away from the electrode assembly, while ensuring that the area of ​​the first section where the first through hole is provided is coated with the first slurry, and drying to obtain a first electrode sheet coated with the first material layer on one side; (4) applying the first slurry on the surface of the first current collector facing the electrode assembly, and drying to obtain a first electrode sheet coated with the first material layer on both sides; (5) after cold pressing and cutting into strips, the first electrode sheet is obtained.

[0063] The present application does not have any special restrictions on the solid content of the above-mentioned first slurry. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application does not have any special restrictions on the process parameters of the above-mentioned drying, cold pressing, cutting, and striping. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. In one or more embodiments, in step (1), while a first through hole is provided on the first section, a second through hole is provided on the third section; in step (4), when the first slurry is coated on the surface of the first current collector facing the electrode assembly, it is ensured that the area of ​​the third section where the second through hole is provided is coated with the first slurry.

[0064] The present application has no particular restrictions on the above-mentioned manner of setting the first through hole and the second through hole, as long as the purpose of the present application can be achieved. For example, the first through hole and the second through hole can be set by pulse laser drilling. The shortest distance m1 between a single first through hole and the first edge or the second edge, the shortest distance m2 between a single second through hole and the first edge or the second edge, the shortest distance a1 between a single first through hole and the third edge, the shortest distance a2 between a single second through hole and the sixth edge, the shortest distance b1 between a single first through hole and the fourth edge, and the shortest distance b2 between a single second through hole and the fifth edge can be controlled by adjusting the spacing between the pulse laser emitters of the pulse laser emitter or the laser emission frequency; the diameter D1 of the maximum circumscribed circle of the outer contour of the single first through hole on the surface of the first current collector, and the diameter D2 of the maximum circumscribed circle of the outer contour of the single second through hole on the surface of the first current collector can be controlled by pulse laser. The power and defocus of the pulse laser emitter can be regulated; the spacing m'1 between two adjacent first through holes and the spacing m'2 between two adjacent second through holes can be regulated by adjusting the spacing between the pulse laser emitters or the laser emission frequency; the proportion S1 of the sum of the areas of the outer contours of multiple first through holes can be regulated by adjusting the surface area of ​​the first segment, the number of first through holes, the power of the pulse laser emitter, the defocus, the spacing between the pulse laser emitters or the laser emission frequency; the proportion S2 of the sum of the areas of the outer contours of multiple second through holes can be regulated by adjusting the surface area of ​​the third segment, the number of second through holes, the power of the pulse laser emitter, the defocus, the spacing between the pulse laser emitters or the laser emission frequency.

[0065] In the present application, the secondary battery also includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no special restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no special restrictions on the content of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no special restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include but is not limited to at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methylcyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0066] In the present application, the secondary battery also includes a diaphragm. The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of a woven film, a non-woven film, a microporous film, a composite film, a rolled film or a spun film. In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application has no particular restrictions on inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene). In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.

[0067] The secondary battery also includes a shell for accommodating the first pole piece, the diaphragm, the second pole piece and the electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0068] The preparation process of the secondary battery of the present application is well known to those skilled in the art and is not particularly limited in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the first electrode sheet, the separator and the second electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery.

[0069] The second aspect of the present application provides an electronic device, comprising the secondary battery in any one of the above embodiments. Therefore, the electronic device of the present application has good performance.

[0070] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0071] Example

[0072] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0073] Test methods and equipment:

[0074] Test of coating thickness:

[0075] The artificial graphite and / or natural graphite with a coating layer was sliced ​​by focused ion beam (FIB) and then characterized by high-resolution transmission electron microscopy (HRTEM, model Talos F200X). Within the same selection range (500,000 times magnification), five positions of the coating layer were randomly selected to measure the thickness of the coating layer in the particles. The arithmetic mean of the thickness of the coating layer at the five different positions was calculated to obtain the average thickness of the coating layer.

[0076] Test of mass percentage of coating layer:

[0077] The artificial graphite and / or natural graphite with coating layer was scanned by laser microconfocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instruments Division) with a test range of 100 cm -1 Up to 4000cm -1 ; and use LabSpec software to process the data and analyze and confirm the type of coating material in the coating layer.

[0078] The artificial graphite and / or natural graphite with coating layer is tested by thermogravimetric analyzer (model: STA499C), wherein the mass loss ratio of the tested sample at 1000°C is the mass percentage of the coating layer.

[0079] Fast-filling graphite performance test:

[0080] Artificial graphite and / or natural graphite with a coating layer, binder styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 85℃ to obtain a negative electrode sheet; the negative electrode sheet was cut into a disc with a diameter of 14mm and used as a working electrode, a metal lithium sheet was used as a counter electrode, and a polyethylene (PE) film with a thickness of 7μm was used as a separator, and a button cell was assembled after injecting the test electrolyte. The button cell was charged and discharged. At an ambient temperature of 25°C, the button cell was charged to 4.35V at 2C constant current, then charged to 0.05C at 4.35V constant voltage, and discharged to 2.4V at 0.5C constant current, and left to stand for 30 minutes. The discharge capacity of the first cycle was recorded, and then 10 charge and discharge cycles were performed, and the discharge capacity of the 10th cycle was recorded. The cycle capacity retention rate of the button cell after 10 cycles was recorded and calculated.

[0081] Cycle capacity retention rate (%) = (discharge capacity at the 10th cycle / discharge capacity at the first cycle) × 100%.

[0082] When the calculated cycle capacity retention rate is ≥80%, the artificial graphite and / or natural graphite with a coating layer can be used as fast-charging graphite and applied to secondary batteries, and the secondary batteries have good fast-charging performance.

[0083] Tests for L1, L2, L3, M, L, m1, m2, a1, a2, b1, b2, m'1, m'2, D1, D2, S1, S2:

[0084] At an ambient temperature of 25°C, the lithium-ion battery was disassembled to obtain an electrode assembly of a winding structure. The first pole piece, as well as the first, second and third sections of the first current collector were located according to the starting position, length and relative relationship of different pole piece material layers. The first pole piece was taken out and soaked in dimethyl carbonate (DMC) for 20 minutes, then placed in an oven and dried at 80°C for 12 hours to obtain a test sample of the first pole piece.

[0085] The first pole piece is unfolded, and the length of the first current collector after unfolding is measured with a tape measure to obtain the length L of the first current collector. The lengths of the first section, the second section, and the third section are measured respectively, and compared with the length L of the first current collector to obtain the values ​​of L1, L2, and L3. The width of the first current collector after unfolding is measured to obtain the width M of the first current collector; the surface area of ​​the first section and the surface area of ​​the third section are calculated based on the above measurement results.

[0086] The coating on the surface of the first pole piece is cleaned off, and an electron scanning microscope is used to measure the diameter D1 of the largest circumscribed circle of the first through hole in the outer contour of the first current collector and the sum of the surface areas of the outer contours of multiple first through holes. At the same time, an electron scanning microscope is used to measure the diameter D2 of the largest circumscribed circle of the second through hole in the outer contour of the first current collector and the sum of the surface areas of the outer contours of multiple second through holes; S1 and S2 are calculated.

[0087] A tape measure is used to measure the spacing m'1 between two adjacent first through holes and the spacing m'2 between two adjacent second through holes along the length direction after the first pole piece is unfolded. A tape measure is used to measure the shortest distance between a single first through hole and the first edge, and the shortest distance between a single first through hole and the second edge along the width direction after the first pole piece is unfolded. The minimum value of the two distances is m1; the shortest distance between a single second through hole and the first edge, and the shortest distance between a single second through hole and the second edge, and the minimum value of the two distances is m2. A tape measure is used to measure the shortest distance a1 between a single first through hole and the third edge, a2 between a single second through hole and the sixth edge, b1 between a single first through hole and the fourth edge, and b2 between a single second through hole and the fifth edge along the length direction after the first pole piece is unfolded.

[0088] Low temperature cycle test:

[0089] The test temperature was maintained at -10°C, and the lithium-ion batteries in the examples and comparative examples were charged to 4.25V at a constant current of 0.1C, then charged to a current of 0.05C at a constant voltage of 4.25V, left to stand for 30 minutes, and discharged to 2.4V at a constant current of 0.5C, left to stand for 30 minutes. The above steps were recorded as one cycle, and each group of lithium-ion batteries was cycled 10 times. After the cycle was completed, each group of lithium-ion batteries was disassembled, the negative electrode plates were taken out, and the states of the negative electrode material layers in different regions on each group of negative electrode plates were observed and recorded.

[0090] The demolding state of the non-lithium intercalation area in the lithium-ion battery is determined based on the demolding area ratio, wherein the demolding area ratio is calculated based on the total area of ​​the material layer in the non-lithium intercalation area.

[0091] Example 1

[0092] <Preparation of positive electrode sheet>

[0093] The positive electrode sheet is used as the second electrode sheet. The positive electrode active materials lithium iron manganese phosphate (LFMP), conductive carbon black (SuperP), and polyvinylidene fluoride (PVDF) are mixed at a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a first positive electrode slurry with a solid content of 65wt%, and stirred evenly. The positive electrode active material nickel cobalt manganese ternary material (LiNi 0.6 Co 0.2 Mn 0.2 O2), conductive carbon black (Super P), conductive carbon nanotubes (CNT), polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.0:0.5:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a second positive electrode slurry with a solid content of 75wt%, and stirred evenly. A 13μm thick aluminum foil is selected as the positive electrode current collector, and the slurry is evenly coated on the positive electrode current collector. The first positive electrode slurry is coated on the side close to the positive electrode current collector, and dried at 90°C to form a lithium iron manganese phosphate layer. The second positive electrode slurry is coated on the upper layer of the material layer formed by the first positive electrode slurry, and dried at 90°C to form a nickel-cobalt-manganese ternary material layer. That is, the single-side coating of the positive electrode sheet is completed, and the coating of the other side is completed in the same way. After the coating is completed, cold pressing is carried out, followed by auxiliary processes such as pole ear welding and adhesive tape, that is, the entire preparation process of the double-sided coated positive electrode sheet is completed. Among them, the coating weight of lithium manganese iron phosphate layer is 75mg / 1540.24mm 2 ; The coating weight of the nickel-cobalt-manganese ternary material layer is 180mg / 1540.24mm 2 The compaction density of the single-side positive electrode material layer is 3.0g / cm 3 There are some empty foil areas of the positive electrode current collector with pole ears, the specifications of the positive electrode current collector with the positive electrode material layer are 1940mm×95mm, the specifications of the single-sided positive electrode material layer are 1940mm×95mm, and the specifications of the positive electrode sheet are 1940mm×95mm.

[0094] <Preparation of negative electrode sheet>

[0095] The negative electrode sheet was used as the first electrode sheet. A copper foil with a thickness of 6 μm was selected as the negative electrode current collector, and the negative electrode current collector and the prepared positive electrode sheet were pre-wound to determine the surface of the negative electrode current collector facing the electrode assembly, the surface away from the electrode assembly, and the first, second, and third sections. Based on the length of the negative electrode current collector, the length of the first section accounted for 10% of L1, the length of the second section accounted for 80% of L2, and the length of the third section accounted for 10% of L3. The shortest distance between a single first through hole and the first edge is set to 3mm, the shortest distance between a single first through hole and the second edge is set to 3mm, the shortest distance between a single first through hole and the third edge is set to 5mm, the shortest distance between a single first through hole and the fourth edge is set to 2.5mm, the diameter D1 of the maximum circumscribed circle of the outer contour of a single first through hole on the surface of the negative electrode current collector is 12μm, along the length direction of the first pole piece after unfolding, the spacing m'1 between two adjacent first through holes is 0.024mm, along the width direction of the first pole piece after unfolding, 4000 rows of first through holes are set, based on the surface area of ​​the first section, the sum of the outer contour areas of multiple first through holes accounts for S1 of 18%. Laser drilling is performed on the first section according to the above setting parameters. Among them, the length L of the negative electrode current collector is 2000mm and the width M is 100mm.

[0096] The artificial graphite coated with carbon nanotubes is used as the negative electrode active material, wherein the average thickness of the coating layer is 50nm; based on the mass of the negative electrode active material, the mass percentage of the coating layer is 7%, and the cycle capacity retention rate of the button battery composed of artificial graphite coated with carbon nanotubes is 86%. The negative electrode active material, conductive carbon black (Super P), and styrene-butadiene rubber (SBR) are mixed according to a weight ratio of 97:1.5:1.5, and deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 57wt%, and stir evenly. The negative electrode slurry is evenly coated on the negative electrode current collector perforated according to the setting, and dried at 110°C to complete the single-sided coating of the negative electrode plate, and then the coating of the other side is completed in the same way. After the coating is completed, cold pressing is performed, followed by auxiliary processes such as pole ear welding and adhesive tape, that is, the entire preparation process of the double-sided coated negative electrode plate is completed. Among them, the coating weight of the negative electrode material layer is 135mg / 1540.24mm 2 The compaction density of the single-sided negative electrode material layer is 1.6g / cm 3 The capacity of active material per unit mass of the negative electrode is 340 mAh / g, the specification of the negative electrode material layer facing the center of the electrode assembly winding is 2000mm×100mm, the specification of the negative electrode material layer facing away from the center of the electrode assembly winding is 2000mm×100mm, there are some empty foil areas of the negative electrode collector with pole ears, the specification of the negative electrode collector with the negative electrode material layer is 2000mm×100mm, and the specification of the negative electrode sheet is 2000mm×100mm.

[0097] <Preparation of Electrolyte>

[0098] In a dry argon atmosphere, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were first mixed in a mass ratio of EC:EMC:DEC=30:50:20 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added to the base solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.

[0099] <Diaphragm>

[0100] A polyethylene (PE) film with a thickness of 9 μm is used as the base film, and the ceramic particles aluminum oxide (Al2O3), the ceramic coating binder styrene-butadiene rubber, and the solvent deionized water are mixed in a mass ratio of 35:10:55 to obtain a ceramic coating slurry. It is coated on one surface of the base film, and after drying at 60°C, a ceramic coating with a thickness of 2 μm is formed on one surface of the base film; the polymer polyvinylidene fluoride (PVDF) and the thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 98.5:1.5, and deionized water is added as a solvent. After stirring evenly, a polymer layer slurry is formed. The polymer layer slurry is coated on the surface of the ceramic coating away from the base film, and a polymer coating is obtained after drying, that is, a diaphragm is prepared. Among them, the coating weight of the polymer coating is 1.5 mg / 1540.25 mm 2 .

[0101] <Preparation of lithium-ion batteries>

[0102] The structure formed by fixing the prepared positive electrode sheet and the separator to the negative electrode sheet is stacked in order and wound into an electrode assembly. After top sealing and side sealing, liquid injection is performed, and the lithium-ion battery after liquid injection is formed (charged at a constant current of 0.02C to 3.3V, and then charged at a constant current of 0.1C to 3.6V), and finally a lithium-ion battery is obtained.

[0103] Examples 2 to 3

[0104] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1.

[0105] Example 4

[0106] Except that in <Preparation of Negative Electrode Sheet>, when the first through hole is laser-formed on the first segment of the negative electrode current collector, the second through hole is laser-formed on the third segment according to the preparation parameters in Table 1, the rest is the same as Example 1.

[0107] Example 5 to Example 23

[0108] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 4.

[0109] Comparative Example 1

[0110] Except that the negative electrode plate is not laser-drilled, the rest is the same as Example 1.

[0111] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.

[0112] Table 1

[0113] Note: “ / ” in Table 1 indicates no relevant preparation parameters.

[0114] It can be seen from Examples 1 to 23 and Comparative Example 1 that by providing a first through hole in the area where the first material layer is provided in the first section, the problem of material layer peeling in the non-lithium intercalation area during low-temperature cycling of the fast-charging graphite system can be effectively improved. In Comparative Example 1, no through holes are provided on the negative electrode plates; the lithium-ion battery in Comparative Example 1 has a large proportion of demolding and lithium deposition areas in the non-lithium intercalation area during low-temperature cycling, indicating that the lithium-ion battery has a serious problem of demolding in the non-lithium intercalation area during the cycling process. However, the lithium-ion batteries in Examples 1 to 23 have a small proportion of demolding areas in the non-lithium intercalation area during low-temperature cycling, indicating that the lithium-ion battery of the present application is conducive to improving the problem of solvent co-embedding in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0115] The length ratio of the first section usually affects the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. From Examples 1 to 3, it can be seen that when the length ratio of the first section is within the scope of this application, the demolding area ratio of the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling is relatively small, indicating that the lithium-ion battery of this application is conducive to improving the problem of solvent co-intercalation in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0116] The length ratio of the third section usually affects the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. It can be seen from Examples 1, 4 to 6 that when the length ratio of the third section is within the scope of this application, the demolding area ratio of the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling is relatively small, indicating that the lithium-ion battery of this application is conducive to improving the problem of solvent co-intercalation in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0117] The values ​​of m1 and m2 usually affect the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. It can be seen from Example 4, Example 7 to Example 10 that when the values ​​of m1 and m2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling accounts for a relatively small proportion, indicating that the lithium-ion battery of this application is beneficial to improving the problem of solvent co-embedding in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold. Among them, in Example 7, when the values ​​of m1 and m2 are 0 respectively, at this time, the first through hole and the second through hole are too close to the edge of the first current collector in the width direction, which can easily increase the powder loss during processing and affect the processing performance of the pole piece.

[0118] The values ​​of a1 and a2 usually affect the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. It can be seen from Example 4, Example 11 to Example 14 that when the values ​​of a1 and a2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling accounts for a relatively small proportion, indicating that the lithium-ion battery of this application is beneficial to improving the problem of solvent co-embedding in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold. Among them, in Example 11, when the values ​​of a1 and a2 are 0 respectively, at this time, the first through hole and the second through hole are too close to the edge of the first current collector in the length direction, which can easily increase the powder loss during processing and affect the processing performance of the pole piece.

[0119] The values ​​of b1 and b2 usually affect the demolding and lithium deposition of the non-lithium intercalation area of ​​the lithium-ion battery. From Examples 4, 15 to 17, it can be seen that when the values ​​of b1 and b2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery is relatively small during low-temperature cycling, indicating that the lithium-ion battery of this application is beneficial to improving the problem of solvent co-intercalation in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0120] The values ​​of D1 and D2 usually affect the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. It can be seen from Example 4, Example 18 to Example 21 that when the values ​​of D1 and D2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling accounts for a relatively small proportion, indicating that the lithium-ion battery of this application is beneficial to improving the problem of solvent co-embedding in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold. Among them, in Example 21, when the values ​​of D1 and D2 are 50 respectively, at this time, the diameter of the maximum circumscribed circle of the outer contour of the first through hole and the second through hole on the surface of the first current collector is larger, and more electrolyte passes through. At this time, the side reactions of the electrolyte and the active material increase, which can easily affect the film formation on the surface of the electrode, thereby affecting the kinetic performance of the lithium-ion battery.

[0121] The values ​​of m'1 and m'2 usually affect the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. It can be seen from Examples 4, 18 to 23 that when the values ​​of m'1 and m'2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling accounts for a relatively small proportion, indicating that the lithium-ion battery of this application is beneficial to improving the problem of solvent co-intercalation in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0122] The values ​​of S1 and S2 usually affect the demolding of the non-lithium intercalation area of ​​the lithium-ion battery. From Examples 4 to 11 and 19 to 24, it can be seen that when the values ​​of S1 and S2 are within the range of this application, the demolding area of ​​the non-lithium intercalation area of ​​the lithium-ion battery during low-temperature cycling accounts for a relatively small proportion, indicating that the lithium-ion battery of this application is conducive to improving the problem of solvent co-intercalation in the non-lithium intercalation area of ​​the lithium-ion battery causing the material layer in the non-lithium intercalation area to peel off and demold.

[0123] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0124] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0125] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A secondary battery, comprising an electrode assembly of a winding structure, the electrode assembly comprising a first pole sheet and a second pole sheet, the first pole sheet comprising a first current collector, the second pole sheet comprising a second current collector, along the length direction of the first pole sheet after unfolding, the first current collector comprising a first section, and along the winding direction of the electrode assembly, the first section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; The first pole piece further comprises a first material layer, the first material layer is disposed on at least a portion of the surface of the first section away from the winding center of the electrode assembly, and a plurality of first through holes are disposed at the location where the first material layer is disposed in the first section; The second pole sheet further includes a second material layer. In the winding structure, the second material layer is disposed on a surface of the second current collector that is away from the winding center of the electrode assembly and opposite to the plurality of first through holes.

2. The secondary battery according to claim 1, wherein Based on the length of the first current collector, the length of the first segment accounts for L1, 2%≤L1≤20%.

3. The secondary battery according to claim 1 or 2, wherein: Along the length direction of the first pole piece after unfolding and in the opposite direction of the winding direction, the first current collector further includes a second section and a third section connected in sequence, the second section is connected to the first section, and in the winding structure, the third section is a portion of at least one surface of the first current collector that is not opposite to the second current collector; The first material layer is disposed on at least a portion of the surface of the third section facing the winding center of the electrode assembly, and a plurality of second through holes are disposed at the location where the first material layer is disposed in the third section; The second material layer is disposed on a surface of the second current collector facing the winding center and opposite to the plurality of second through holes.

4. The secondary battery according to claim 3, wherein Based on the length of the first current collector, the length of the third segment accounts for L3, 2%≤L3≤20%.

5. The secondary battery according to claim 3, wherein Along the width direction of the first pole piece after unfolding, the first current collector has a first edge and a second edge opposite to each other, the width of the first current collector is M mm, the shortest distance between a single first through hole and the first edge or the second edge is m1 mm, 0≤m1≤M / 10; and / or, The shortest distance between a single second through hole and the first edge or the second edge is m2 mm, 0≤m2≤M / 10.

6. The secondary battery according to claim 5, wherein 1≤m1≤M / 20; and / or, 1≤m2≤M / 20.

7. The secondary battery according to any one of claims 3 to 6, wherein Along the length direction of the unfolded first pole sheet and along the winding direction of the electrode assembly, the first section has a third edge and a fourth edge opposite to each other, the third section has a fifth edge and a sixth edge opposite to each other, the length of the first current collector is L mm, the shortest distance between a single first through hole and the third edge is a1 mm, 0≤a1≤(L1×L) / 10; and / or, The shortest distance between a single second through hole and the sixth edge is a2 mm, and 0≤a2≤(L3×L) / 10.

8. The secondary battery according to claim 7, wherein 1≤a1≤(L1×L) / 20; and / or, 1≤a2≤(L3×L) / 20.

9. The secondary battery according to claim 7, wherein The shortest distance between a single first through hole and the fourth edge is b1 mm, 0≤b1≤(L1×L) / 20; and / or, The shortest distance between a single second through hole and the fifth edge is b2 mm, and 0≤b2≤(L3×L) / 20.

10. The secondary battery according to claim 9, wherein 0≤b1≤(L1×L) / 40; and / or, 0≤b2≤(L3×L) / 40.

11. The secondary battery according to any one of claims 3 to 10, wherein The diameter of the maximum circumscribed circle of the outer contour of a single first through hole on the surface of the first current collector is D1 μm, 2≤D1≤50; and / or, The diameter of the maximum circumscribed circle of the outer contour of a single second through hole on the surface of the first current collector is D2 μm, and 2≤D2≤50.

12. The secondary battery according to claim 11, wherein 5≤D1≤20; and / or, 5≤D2≤20.

13. The secondary battery according to any one of claims 3 to 12, wherein: Along the length direction of the first pole piece after unfolding, the distance between two adjacent first through holes is m'1 mm, 1.5D1≤m'1≤3D1; and / or, The distance between two adjacent second through holes is m'2 mm, and 1.5D2≤m'2≤3D2.

14. The secondary battery according to any one of claims 3 to 13, wherein Based on the surface area of ​​the first section, the sum of the areas of the outer contours of the plurality of first through holes accounts for S1, 5%≤S1≤30%; and / or, Based on the surface area of ​​the third segment, the sum of the areas of the outer contours of the plurality of second through holes accounts for S2, 5%≤S2≤30%.

15. The secondary battery according to claim 14, wherein 13%≤S1≤18%; and / or, 13%≤S2≤18%.

16. The secondary battery according to any one of claims 3 to 15, wherein The first material layer is disposed on the entire surface of the first section away from the winding center of the electrode assembly; and / or, The first material layer is disposed on at least a portion of the surface of the first section facing the winding center of the electrode assembly; and / or, The first material layer is disposed on the entire surface of the third section toward the winding center of the electrode assembly; and / or, The first material layer is disposed on at least a portion of the surface of the third section facing away from the winding center of the electrode assembly.

17. The secondary battery according to any one of claims 1 to 16, wherein The first pole piece is a negative pole piece. 18 . An electronic device comprising the secondary battery according to claim 1 .